2011
DOI: 10.1089/ars.2010.3526
|View full text |Cite
|
Sign up to set email alerts
|

Both Maximal Expression of Selenoproteins and Selenoprotein Deficiency Can Promote Development of Type 2 Diabetes-Like Phenotype in Mice

Abstract: Selenium (Se) is an essential trace element in mammals that has been shown to exert its function through selenoproteins. Whereas optimal levels of Se in the diet have important health benefits, a recent clinical trial has suggested that supplemental intake of Se above the adequate level potentially may raise the risk of type 2 diabetes mellitus. However, the molecular mechanisms for the effect of dietary Se on the development of this disease are not understood. In the present study, we examined the contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
130
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(144 citation statements)
references
References 38 publications
(51 reference statements)
9
130
1
Order By: Relevance
“…Furthermore, these symptoms worsened when animals were subjected to Se deficiency leading to development of obesity and hypercholesterolemia (309). The data suggest that the metabolic perturbations caused by the lack of SCL might be due to defects in selenoprotein synthesis and are in line with the recently observed link between selenoprotein deficiency and disrupted glucose homeostasis in mice (198). It remains to be tested which selenoproteins are most involved in the development of this phenotype in mice lacking SCL.…”
Section: E Sec Lyasesupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, these symptoms worsened when animals were subjected to Se deficiency leading to development of obesity and hypercholesterolemia (309). The data suggest that the metabolic perturbations caused by the lack of SCL might be due to defects in selenoprotein synthesis and are in line with the recently observed link between selenoprotein deficiency and disrupted glucose homeostasis in mice (198). It remains to be tested which selenoproteins are most involved in the development of this phenotype in mice lacking SCL.…”
Section: E Sec Lyasesupporting
confidence: 59%
“…In accordance with these observations, the results of several clinical trials that investigated the chemopreventive effects of dietary Se supplementation revealed that increased intake of Se above the nutrient requirements may raise the risk of type 2 diabetes mellitus in humans (222,327). Although the exact mechanism of the diabetogenic effect of high Se intake remains unclear, increased expression of GPx1, SelP, MsrB1, and SelS has been implicated in the development of type 2 diabetes and insulin resistance (198,256,287,382). At least some of these effects could be attributed to diminished intracellular H 2 O 2 levels as a result of high GPx1 activity leading to suppression of insulin signaling and increased insulin secretion, similar to GPx1-overexpressing mice (386).…”
Section: Selenoprotein Functionmentioning
confidence: 67%
“…Further, transgenic mice overexpressing Gpx1 developed a type-2 diabetes-like phenotype characterized by insulin resistance, hyperglycemia, hyperinsulinemia, and obesity (161). In fact, perturbing the axis of selenoprotein expression toward either deficient or over-expressed levels may dysregulate glucose homeostasis and promote the development of diabetes (139).…”
Section: J Se Supplementation and Inflammation Associated With Diabetesmentioning
confidence: 99%
“…Conversely, mice with a targeted deletion of another selenoprotein gene, the type 2 deiodinase (Dio2), were observed to have increased adiposity and to be less responsive to insulin stimulation in comparison with wild-type mice (20). Also, studies on transgenic mice in which selenoprotein expression was reduced by overexpression of a mutant i 6 A Ϫ selenocysteine tRNA revealed impaired glycemic control and increased insulin levels in these mutant mice relative to controls (21). Recent findings in this laboratory have documented that mice lacking selenocysteine lyase, an enzyme involved in cellular selenium recycling, exhibit diminished selenoprotein expression and develop metabolic syndrome when fed a low selenium diet (22).…”
Section: Discussionmentioning
confidence: 99%